(untitled) (diségno, 2018)
In 2018, the 40th Conference of Teachers of Representation Disciplines took place in Milan: the first edition of these meetings was held on 3-4-5 May 1979 in Santa Margherita Ligure. The Italian Union for Drawing (UID) will appropriately remember this recurrence, effectively kicking off a two-year celebration, considering that the 40th anniversary of the foundation of our scientific society (formally constituted on August 4, 1980) will fall in 2020 (read more).